2012
DOI: 10.1002/cne.23117
|View full text |Cite
|
Sign up to set email alerts
|

Phox2b expression in the taste centers of fish

Abstract: The homeodomain transcription factor Phox2b controls the formation of the sensory-motor reflex circuits of the viscera in vertebrates. Among Phox2b-dependent structures characterized in rodents is the nucleus of the solitary tract, the first relay for visceral sensory input, including taste. Here we show that Phox2b is expressed throughout the primary taste centers of two cyprinid fish, Danio rerio and Carassius auratus, i.e., in their vagal, glossopharyngeal, and facial lobes, providing the first molecular ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 104 publications
1
15
0
Order By: Relevance
“…The homeodomain transcription factor Phox2b is also essential for glomus cell development (Dauger et al, 2003). However, we were unable to detect Phox2b-positive cells in embryonic zebrafish gills or orobranchial epithelium at 5-dpf (n = 4) or 7-dpf (n = 3), although Phox2b was expressed by a subset of cells in the hindbrain, as expected (Coppola et al, 2012) (Figure 6a–f’). Similarly, we could not detect any Phox2 -positive cells in sea lamprey gills or orobranchial epithelia at E16 or E18 (n = 6), although Phox2 was expressed in the epibranchial ganglia, and in patches of ectoderm and subjacent mesenchyme ventral to the epibranchial ganglia (Figure 6g–j’), in the same position as the hypobranchial placodes and associated ganglia identified in Xenopus (Schlosser, 2003).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The homeodomain transcription factor Phox2b is also essential for glomus cell development (Dauger et al, 2003). However, we were unable to detect Phox2b-positive cells in embryonic zebrafish gills or orobranchial epithelium at 5-dpf (n = 4) or 7-dpf (n = 3), although Phox2b was expressed by a subset of cells in the hindbrain, as expected (Coppola et al, 2012) (Figure 6a–f’). Similarly, we could not detect any Phox2 -positive cells in sea lamprey gills or orobranchial epithelia at E16 or E18 (n = 6), although Phox2 was expressed in the epibranchial ganglia, and in patches of ectoderm and subjacent mesenchyme ventral to the epibranchial ganglia (Figure 6g–j’), in the same position as the hypobranchial placodes and associated ganglia identified in Xenopus (Schlosser, 2003).…”
Section: Resultssupporting
confidence: 55%
“…Primary antibodies were used against the following antigens: acetylated tubulin [1:250 mouse IgG2b, clone 6-11-B1, T7451 Sigma-Aldrich; previously used in the sea lamprey, e.g., Barreiro-Iglesias et al (2008a)], Ascl1 (Mash1) [1:200 mouse IgG1 (Lo et al, 1991), kind gift of F. Guillemot, NIMR, London, UK; 1:100 mouse IgG1, #556604 BD Biosciences, San Jose, CA], DsRed2 (1:100 mouse IgG1, sc-101526 Santa Cruz Biotechnology, Dallas, TX), Elavl3/4 (HuC/D) (1:500 mouse IgG2b, A-21271 Invitrogen), GFP (1:500 rabbit, A-6455 Invitrogen; 1:500 mouse IgG1, #1814460001 Roche, Basel, Switzerland; 1:250 goat, ab6662 Abcam [Cambridge, UK]; 1:150 chicken, ab13970 Abcam), HNK-1 carbohydrate epitope (Abo and Balch, 1981; Voshol et al, 1996) [for zebrafish neurites (Metcalfe et al, 1990): 1:100 mouse IgG1, ZN-12 Developmental Studies Hybridoma Bank; for lamprey neurites (Barreiro-Iglesias et al, 2008b): 1:50 mouse IgM, 3H5 Developmental Studies Hybridoma Bank], mCherry (1:250 mouse IgG1, #632543 Clontech Takara Bio USA Inc., Mountain View, CA; 1:200 goat, orb11618 Biorbyt, Cambridge, UK), serotonin (5-hydroxytryptamine, 5-HT) [1:100 (whole-mount) or 1:250 (sections) rabbit, S5545 Sigma-Aldrich, previously used in zebrafish, e.g., Kuscha et al (2012), bullfrog (Reyes et al, 2014) and Arctic lamprey (Suzuki et al, 2015); 1:100 rat, MAB352 Merck Millipore, Temecula, CA, previously used in zebrafish (Sundvik et al, 2013); 1:250 goat, ab66047 Abcam], Phox2b [1:500 rabbit, kind gift of Jean-François Brunet, Institut de Biologie de l'École Normale Supérieure, Paris, France; previously used in zebrafish (Coppola et al, 2012); Tubb3 (neuronal β-III tubulin) (1:500 mouse IgG2a, clone TUJ1, MMS-435P Covance BioLegend, San Diego, CA), and tyrosine hydroxylase [1:250, rabbit, AB152 Merck Millipore; previously used in zebrafish, e.g., Yamamoto et al (2011), and sea lamprey, e.g., Barreiro-Iglesias et al (2008a). (The Developmental Studies Hybridoma Bank was developed under the auspices of the NICHD and is maintained by the University of Iowa, Department of Biological Sciences, Iowa City.)…”
Section: Methodsmentioning
confidence: 99%
“…Expression of Isl1 has been shown partially to overlap that of HCN4 in the zebrafish heart (Tessadori et al, 2012), so we have included an analysis of the distribution of immunoreactivity for this factor in our study. The anti-Isl1 antibody used here (AB_19412957; Developmental Studies Hybridoma Bank) was the same as that used by Tessadori et al (2012) and others in zebrafish (see, e.g., Kuscha et al, 2012), and its pattern of expression matches the labeling of motor neurons in in situ hybridization experiments in the hindbrain of developing zebrafish (Coppola et al, 2012). These authors also showed that anti-Isl1 antibody detection was eliminated after injection of morpholinos directed against Isl1 and by preabsorption with Isl1 peptide (Moreno et al, 2008(Moreno et al, , 2012.…”
Section: Antibody Specificitymentioning
confidence: 97%
“…In the carp and goldfish vagal lobes, interneurons and motoneurons have also been studied with neuronal tracing (Morita and Finger, ; Ikenaga et al, ) and immunohistochemistry (Ikenaga et al, ; Giráldez‐Pérez et al, 2009; Coppola et al, ). A recent study has shown that the homeodomain transcription factor Phox2b is expressed throughout development in the vagal, glossopharyngeal, and facial sensory lobes of goldfish and zebrafish (Coppola et al, ), providing clear molecular evidence for homology of these teleost taste nuclei and the nucleus of the solitary tract of mammals. With regard to the adult zebrafish, the organization of primary taste nuclei is primarily known from comparisons with carp and goldfish, consisting of a large medial facial lobe and two large paired vagal lobes, whereas the small glossopharyngeal lobes are closely associated with the vagal lobes and the facial lobe (Wullimann et al, ; Rupp et al, ).…”
mentioning
confidence: 99%